A comparative study of the translation profession in Malaysia and Korea / Kang Myoung Sook - Kang, Myoung Sook (2015)
The translation profession is regarded as one of the emerging professions in present times owing to its increasingly important role in disseminating information between various nations and cultures of the world. Nevertheless, translators face numerous obstacles in their quest to be recognized as full-fledged professionals. This study endeavors to provide a comparative description of the current status of the translation profession in Malaysia and Korea and to highlight the issues and challenges affecting the profession in both these countries. Past research has shown that translators from both developed and developing countries face many challenges in their practice. Amongst the problems which translators face are low pay, inconsistency in the code of conduct adhered to and the absence of quality control standards. Most translators’ associations in countries around the world do not have authority over their members and do not regulate their practice. Past studies also reveal that many societies do not regard translators as true professionals in their country. This study intends to ascertain if these issues are also real concerns in Malaysia and Korea. This research adopts an empirical, qualitative-oriented approach known as hermeneutic phenomenology. This approach seeks to describe, interpret and explain the phenomenon studied. In this study, the current status of translation profession in Malaysia and Korea is the phenomena which will be described, and the researcher would seek to interpret and explain the phenomena presented. Three research instruments that is, a survey questionnaire, interviews and document review were used to collect the data. Results from both countries were compared to highlight similarities and differences in a number of core aspects of the translation profession. This research has revealed that the Korean respondents possess higher academic qualifications but experience less self-satisfaction in the translation profession compared to their Malaysian counterparts. However, respondents from both countries similarly express indifference towards engaging in continuing professional development (CPD) activities and in using an external quality standard. Although the Malaysian and Korean translators regard themselves as professionals in society, clients who seek out translators and the public in general have very little awareness about the role and work of a translator. The translators also cited challenges such as unfair competition from amateur translators and unprofessional practices in their profession. These challenges are linked to the translators’ associations in both countries not wielding sufficient authority in regulating the practice of its members and protecting the rights of the trained translators. The comparison of the translation profession in Malaysia and Korea against Tseng’s Model of Professionalization Process revealed that in both countries, the profession is at the transition stage from the market disorder phase to the consolidation phase. A new model of the professionalization process for the translation profession has been proposed by the researcher based on the suggestions put forth by the respondents and the findings of this research. There is most importantly a need for translation associations to be endowed with the authority to regulate the practice of their members. With such authority translation can become an exclusive profession, where only those who have the qualification and competence in translating are admitted into a professional body and are allowed to practice. Nevertheless, it is also important for the translators to adhere to a code of practice, external quality standards and to engage in CPD activities in order to ensure the sustained competence of translators and subsequently, the elevation of the translation profession to a full professional status.